Communal individualism: A critical analysis of the nature of African community - Biar, Zechariah Manyok (Stellenbosch theological journal, 2023)
An African community appears to function in the same way that an individual functions in the (post)modern West. It differs from an understanding of ubuntu and an African community as universal. This article diverges from the universalised concept of ubuntu in that it points out that the rural understanding of a community in Africa is more local than universal. The explored literature seems to support the rural understanding of an African community as more local and exclusive than universal and inclusive. Blood relationships and shared practices define this particularised identity. The article, therefore, recommends that the individual concept of an African community would be universalised only when it is applied to Christianity as a universal community of believers united by the blood of Jesus.